If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4.5(3x+)-2x=7x-3(-2x+11)
We move all terms to the left:
4.5(3x+)-2x-(7x-3(-2x+11))=0
We add all the numbers together, and all the variables
4.5(+3x)-2x-(7x-3(-2x+11))=0
We add all the numbers together, and all the variables
-2x+4.5(+3x)-(7x-3(-2x+11))=0
We multiply parentheses
-2x+13.5x-(7x-3(-2x+11))=0
We calculate terms in parentheses: -(7x-3(-2x+11)), so:We add all the numbers together, and all the variables
7x-3(-2x+11)
We multiply parentheses
7x+6x-33
We add all the numbers together, and all the variables
13x-33
Back to the equation:
-(13x-33)
11.5x-(13x-33)=0
We get rid of parentheses
11.5x-13x+33=0
We add all the numbers together, and all the variables
-1.5x+33=0
We move all terms containing x to the left, all other terms to the right
-1.5x=-33
x=-33/-1.5
x=+22
| 20(-15x+24)=17(x-3) | | 60/;m=5 | | 20(-13x+21)=17(x-3) | | 15x-+20-2x=7x+6x-33 | | n+1-4n=-1 | | 20(−13x+21)=17(x−3) | | 14(3x-15)=24(x+4) | | 14(3x−15)=24(x+4) | | 20(11x-25)=33(x+2) | | r=250/4000(3/12) | | 17x-14=2x+5+12 | | -1+8x=2(9x+14)-x | | 2/7x+x/3=10/21 | | 14+18x=3(4x+3)-x | | 35r-21=35r+19 | | 2+9x=5(6x+31)+x | | (3x+10)=(2x+15)=180 | | -1+z/2=9 | | -11/2x+3/4x=-57/2 | | (15)•2x=x | | 77=(3z-1) | | 9+2x=2(8x+23)+x | | 5/7=n/28 | | 5(8e−6)−6=364 | | 5^x=300 | | 7+17x=4(22x+2)x | | 7+17x=4(22x | | 2.3n=8,281 | | 8x2-4x-18=0 | | 10.5+3a=5a+2.5 | | 4e+7=2e+9 | | 7+17x=4(22x+2)+x |